The effect of 5′ and 3′ non-translated regions on the expression of a transgene from a Newcastle disease virus vector - Ishita Roy Chowdhury; Ekaterina Viktorova; Siba K. Samal; George A. Belov (Virus Research, 2024)
Newcastle disease virus (NDV) is an avian virus and a promising vector for the development of vaccines for veterinary and human use. The optimal vaccine vector performance requires a stable high-level expression of a transgene. The foreign genes are usually incorporated in the genome of NDV as individual transcription units, whose transcription and subsequent translation of the mRNA are regulated by the 5′ and 3′ untranslated regions (UTRs) flanking the open reading frame of the transgene. Here, we investigated if the UTRs derived from the cognate NDV genes would increase the expression of a model protective antigene from an NDV vector. Our results show that in chicken DF1 cells, none of the UTRs tested significantly outperformed generic short sequences flanking the transgene, while in human HeLa cells, UTRs derived from the M gene of NDV statistically significantly increased the expression of the transgene. The UTRs derived from the HN gene significantly downregulated the transgene expression in both cell cultures. Further experiments demonstrated that NDV UTRs differently affect the mRNA abundance and translation efficacy. While both M and HN UTRs decreased the level of the transgene mRNA in infected cells compared to the mRNA flanked by generic UTRs, M, and particularly, HN UTRs strongly increased the mRNA translation efficacy. The major determinants of translation enhancement are localized in the 5′UTR of HN. Thus, our data reveal a direct role of NDV UTRs in translational regulation, and inform future optimization of NDV vectors for vaccine and therapeutic use.